Semantic Technologies in Content Management Systems Trends, Applications and Evaluations - Maass, Wolfgang; Kowatsch, Tobias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Content Management Systems (CMSs) are used in almost every industry by millions of end-user organizations. In contrast to the 90s, they are no longer used as isolated applications in one organization but they support critical core operations in business ecosystems. Content management today is more interactive and more integrative: interactive because end-users are increasingly content creators themselves and integrative because content elements can be embedded into various other applications. The authors of this book investigate how Semantic Technologies can increase interactivity and integration capabilities of CMSs and discuss their business value to millions of end-user organizations. This book has therefore the objective, to reflect existing applications as well as to discuss and present new applications for CMSs that use Semantic Technologies. An evaluation of 27 CMSs concludes this book and provides a basis for IT executives that plan to adopt or replace a CMS in the near future.
Keywords: Business; Industrial management; Management; Information technology; Business -- Data processing; Information storage and retrieval; Management information systems; Computer science; Business and Management; Innovation/Technology Management; IT in Business; Media Management; Management of Computing and Information Systems; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Electronic books